Защитная роль надмьщелкового отверстия плечевой кости для срединного нерва позвоночных - Ильенко, Н.Н. (Вестник зоологии, 1977)
The article deals with analysis of the humurus structure and topographic peculiarities of the median nerve in the elbow joint area in representatives of four classes of vertebrates. The protective role of the humerus picondylic foramen for the median nerve of some mammals was considered from the positions of the character of adaptation changes in extremities to the substrate.